CatUX: Guia para uso de métodos e técnicas de UX Research para profissionais de startups de software - Bianchini, Luana de Parolis (Universidade Federal de São Carlos, 2023)
Software startups differ from established companies because they are organizations that work with innovative products, having a high degree of growth and at the same time dealing with financial uncertainties, lack of time, limited trained professionals and running a high risk of instability in the market. Many startups end up closing in the first few years because they are unable to manage their uncertainties and deliver efficient and differentiated products. Among the various tools that can help these professionals to enrich their products and connect them to their customers, User eXperience methods and techniques are being alternatives to maintain the high quality level of the software. Studies indicate that, for many professionals, UX is an area that is still unexplored, requiring training of the team (in which they usually do not have time) or hiring professionals (in which they usually do not have financial resources). The objective of this master's project was to propose a catalog, called CatUX, which has recommendations for UX Research approaches, methods, techniques and tools to help professionals in software startups. The catalog, available in web format, has detailed explanations about the method, which tools to use and how to apply it. CatUX was proposed based on a thematic analysis of the results of a gray literature review. After extracting and validating the information, the final version of CatUX was defined. CatUX was evaluated from two perspectives: catalog usage and catalog acceptance. The result of the evaluation with real users showed that, despite the need for some adjustments, CatUX is useful and helped the participants to choose the most appropriate approach, method, technique and tool for the situation of each proposed scenario.
CatUX: Guide to using UX Research methods and techniques for software startup professionals
Keywords: Experiência do Usuário; Startups de Software; Pesquisa em UX; User eXperience; UX; UX Research; Software Startup; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO